Sustainable Fashion: Upcycling Traditional Palestinian Dresses – Innovative and Sustainable Solutions for Protecting National Heritage - Hadeel Abdellatif (Kurdish Studies, 2023)
The cultural heritage of occupied countries is immensely valuable and a symbol of identity and proof of land ownership and belonging. Especially as these cultures are under threat of obliteration, distortion, and forced concealment. This research delves into the sustainable and innovative solutions created by Palestinian women to upcycle their traditional dresses to protect their heritage and educate younger generations about the Palestinian cause through the fascinating Palestinian embroidery (also known as Tatreez). This is achieved through a qualitative methodology with the use of purposeful sampling to select participants from a mall intercept and were randomly divided into five focus groups of ten. Each group was interviewed in a session. All focus groups were audio-recorded, transcribed, coded, and analyzed using NVIVO 12. Two overarching themes were identified from the focus group sessions; “Conserving and Sustaining Traditional Dress” and “Upcycling Traditional Dresses”. The results revealed that Palestinian women upcycle their traditional dresses by redesigning the dress and re-wearing it, reusing the dress into modern fashion pieces, or reusing the dress into homeware pieces. Further, the results demonstrated that upcycling traditional Palestinian dresses is a sustainable tool for protecting Palestinian heritage, rooting the Palestinian cause in the minds and souls of the new generations, and a sign of the right of return.